INFORMATION TECHNOLOGY IN LOGISTICS. THE TOOLS FOR PROCESSES OPTIMISATION IN MANAGING AN ENTERPRISE – MULTI-CRITERIA OPTIMISATION - Pawęska, Marcin; Popkowski, Tadeusz (Proceedings of National Aviation University (archive), 2018)
The concepts of optimization, optimal, are very natural elements of our normal (everyday, colloquial) vocabulary, which are used – and one can even risk a statement overused - in situations when you want to point to the characteristics of a subject, object or phenomenon that significantly differentiate them in a given class, type or kind. This is, in a sense, an over-interpretation, especially in cases when we do not give, or are unable to indicate the criteria that constitute the essence of the space for assessing the distinguished features of the indicated object. Optimization – the method of determining the best (optimal) solution (searching for the extreme of the function) from the point of view of a given criterion (indicator) of quality (eg cost, road, efficiency). Examples of multi-criteria optimization applications could be multiplied indefinitely, hence only a few obvious examples of a quite general nature: product and production process design, financial management, aircraft design, cars (e.g. maximization of the performance indicator when limiting the vehicle's fuel consumption, or lowering the weight of the device while maximizing the strength of its individual components, etc.), maximizing profits, including the one performed by minimizing production costs. The conditions of crisis management are significantly different, with specific characteristics of the application area of multi-criteria optimization in the decision-making process. The very definition of crisis management determines a certain framework that, on the one hand, corresponds legibly with the idea and principles of multi-criteria optimization, on the other hand, they naturally prefer the indicated criteria defined by the function of the goal. The work presents the essence of the optimization problem in the simplest possible way, including in relation to crisis management conditions.